COVID-19: captures iron and generates reactive oxygen species to damage the human immune system - Liu Wenzhong; Li Hualan (Taylor & Francis Group, 2021)
Currently, the novel coronavirus pneumonia has been widespread globally, and there is no specific medicine. In response to the emergency, we employed bioinformatics methods to investigate the virus's pathogenic mechanism, finding possible control methods. We speculated in previous studies that E protein was associated with viral infectivity. The present study adopted the domain search techniques to analyse the E protein. According to the results, the E protein could bind iron or haem. The iron and haem bound by the E protein came from the attacked haemoglobin and phagocytes. When E protein was attached to haem, it synthesised oxygen and water into superoxide anions, hydrogen peroxide and hydroxyl radicals. When the iron-bound E protein and the haem-bound E protein worked together, they converted superoxide anions and hydrogen peroxide into oxygen and water. These were the "ROS attack" and "ROS escape" of the virus. "ROS attack" damaged the tissues or cells exposed on the surface of the virus, and "ROS escape" decomposed the superoxide anion and hydrogen peroxide that attacked the virus. When NK cells were exposed to infected cells, viruses that had not shed from the infected cells' surface damaged them through "ROS attack". In addition, lymphocytes such as T cells and B cells, which could be close to the antigen of the virus surface, were also easily damaged or killed by the "ROS attack", generating a decrease in lymphocytes. When memory B cells were exposed to the virus's surface antigen, they were also damaged by "ROS attack", resulting in the patient's re-infection. The virus applied the "ROS escape" to decompose hydrogen peroxide released by phagocytes into oxygen and water. The surrounding cells were replenished with oxygen, and the patient was in a "happy hypoxia" state. When the phagocytes swallowed the virus, the E protein converted superoxide anions into oxygen and water. In this way, the virus parasitized in the vesicles of the phagocyte. While virus was in the lysosome, the E protein generated ROS to damage nearby hydrolases. In this way, the virus parasitized the lysosome. Excessive hydroxyl free radicals destroyed the membrane structure of the lysosome, causing the hydrolase release from lysosome, autophagy of phagocytic cells and subsequent cell death. As a result, the colonizing phagocytes of the virus was associated with asymptomatic infection or retest-positive. Briefly, the virus inhibited the immune system through "ROS escape", and damaged the immune system by "ROS attack". The destruction instigated a strong cytokine storm, leading to organ failure and complications.